2016
DOI: 10.1186/s40880-016-0167-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and failure patterns in non-metastatic nasopharyngeal carcinoma after intensity-modulated radiotherapy

Abstract: BackgroundThe prognostic values of staging parameters require continual re-assessment amid changes in diagnostic and therapeutic methods. This study aimed to identify the prognostic factors and failure patterns of non-metastatic nasopharyngeal carcinoma (NPC) in the intensity-modulated radiotherapy (IMRT) era.MethodsWe reviewed the data from 749 patients with newly diagnosed, biopsy-proven, non-metastatic NPC in our cancer center (South China, an NPC endemic area) between January 2003 and December 2007. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 36 publications
6
118
0
Order By: Relevance
“…Most distant metastasis occurs within 3 years after radiotherapy completion, with distant metastasis occurring in 52% of patients in the 1st year, 23% in the 2nd year, and 20% in the 3rd year . To date, although NPC is sensitive to radiotherapy, distant metastasis is the primary cause of treatment failure …”
Section: Introductionmentioning
confidence: 99%
“…Most distant metastasis occurs within 3 years after radiotherapy completion, with distant metastasis occurring in 52% of patients in the 1st year, 23% in the 2nd year, and 20% in the 3rd year . To date, although NPC is sensitive to radiotherapy, distant metastasis is the primary cause of treatment failure …”
Section: Introductionmentioning
confidence: 99%
“…In the 2D‐CRT era, patients with orbit, cranial nerve, intracranial, or medial and lateral pterygoid muscle involvement have poor prognoses, and were classified as T4 disease according to the 7th AJCC staging system . However, only orbit involvement remains a significant prognostic factor for local failure in the IMRT era . Pan et al conducted a retrospective study of 1609 patients with NPC who were staged using MRI and observed no significant differences in OS among those with infiltration of adjacent soft tissues, including the medial and lateral pterygoid muscles, prevertebral muscles and parapharyngeal space .…”
Section: Discussionmentioning
confidence: 99%
“…Lai et al found the improved treatment outcomes for patients treated with IMRT compared to 2D-CRT were primarily due to higher local tumor control, and also demonstrated distant metastasis is now the predominant mode of treatment failure in NPC. 6,19 Hen et al reported that T category had no predictive value for local control and OS, whereas N category was a significant prognostic factor for OS. 19 Therefore, the prognostic value of T category may have become weaker than that of N category due to the excellent local control rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations